2020
DOI: 10.1108/jima-05-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the motives behind the purchase of western imported food products. A phenomenological study from a Muslim-dominated region

Abstract: Purpose The usage and preference of western imported food in a Muslim-majority state signifies its importance and relevance in a specific culture. However, the inclination and preference toward imported food products must be backed by a strong motivation, when the religion of Islam does not permit overspending yet the amount spent on such imported food products is overwhelming. Hence, the purpose of this study is to explore the motivation behind this behavior. Design/methodology/approach This is a qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The authors first performed traditional text mining that refers to the use of human intelligence to manually harvest the information from the sampled documents. The content analysis which has been widely used to discuss various topics in Islamic marketing researches (Baran, 2020; Bukhari et al , 2020; Bukhari et al , 2020; Heidari et al , 2020; Islam, 2020; Muharam and Asutay, 2019; Muneeza and Mustapha, 2020) was employed. Furthermore, an inductive and deductive reasoning as have been used by relevant studies (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The authors first performed traditional text mining that refers to the use of human intelligence to manually harvest the information from the sampled documents. The content analysis which has been widely used to discuss various topics in Islamic marketing researches (Baran, 2020; Bukhari et al , 2020; Bukhari et al , 2020; Heidari et al , 2020; Islam, 2020; Muharam and Asutay, 2019; Muneeza and Mustapha, 2020) was employed. Furthermore, an inductive and deductive reasoning as have been used by relevant studies (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Comot's TWC has a unique shape compared to other brands in general, which was rather squared instead of rounded, unique, and made the product seem crisper. Packaged TWC samples' appearance generated different buying motivations, as stated by Bukhari et al (2022) that purchase behavior was influenced by attractive packaging and information provided on the label. Samples T1 and T2 had the highest motivation values while T3 and T4 were the lowest.…”
Section: Sensory Analysis Resultsmentioning
confidence: 99%
“…The study's findings indicated that factors including spare parts availability, capacity loading, mileage, and after-sales service have a significant influence on consumer experience for light commercial vehicles. Bukhari (2018) conducted research to understand how Pakistani consumers buy western imported foods and discovered that factors such as product pricing, brand personality, self-concept, product characteristic, and brand trust significantly influence consumers' intentions to repurchase the imported foods. Nadzri et al (2016) looked into the national automotive industry's antecedents of brand experience.…”
Section: Literature Reviewmentioning
confidence: 99%